Теоретичні засади інвестиційної діяльності підприємств - Вініченко, Ігор Іванович; Vinichenko, Igor; Полегенька, Марина Анатоліївна; Polehenka, Marina; Сірак, Юлія Віталіївна; Sirak, Julia (Чорноморський національний університет імені Петра Могили, ТОВ `ДКС Центр`, 2022)
В статті визначено, що у багатьох визначеннях інвестиції розглядаються як категорія синтетична, що поєднує такі елементи: заощадження, кошти, майно чи цінності, процеси вкладення чи здійснення витрат, прибуток, дохід, ефект. При цьому головною рушійною силою такої єдності має бути віддача вкладень, досягнення певної наперед поставленої мети. Тобто інвестиції є надзвичайно ємним поняттям, яке утримує основні елементи, визначаючи закономірності функціонування і саморегуляції інвестиційної сфери. Для будь-якої економічної системи інвестиційна діяльність є важливою складовою економіки. Інвестиції є необхідною умовою економічного розвитку; інвестиція передбачає витрати ресурсів і отримання ефекту; можливість отримання ефекту ймовірнісна, ризикована; існує визначене (зазвичай довгострокове) часове відставання між споживанням ресурсів та ефектом. Аргументовано, що інвестиційна діяльність підприємств пов'язана як з науково-дослідними розробками, науковими дослідженнями, підготовкою висококваліфікованого персоналу, так і з придбанням необхідних засобів виробництва, технологічного обладнання, будівництвом інженерних споруд, об'єктів нерухомості тощо. The article identifies that, in many definitions, investments are considered as a synthetic category, combining the following elements: savings, funds, property or values, investment or cost processes, profit, income, effect. The main driving force behind such unity should be the return on investment, the achievement of a certain goal. That is, investment is an extremely capacious concept that holds the basic elements, defining the patterns of functioning and self-regulation of the investment sphere. Investments play an important role in maintaining and building economic potential enterprises. Their income, favorably affects the activities of enterprises, leads to an increase gross regional product, increases the activity of commodity producers in the foreign market. Investment is a prerequisite for economic development; they involves the expenditure of resources and obtaining an effect; the possibility of obtaining an effect is probabilistic, risky; there is a defined (usually long-term) time lag between resource consumption and effect. It is argued that the investment activity of enterprises is connected with research and development, scientific research, training of highly qualified personnel, as well as with the acquisition of necessary means of production, technological equipment, construction of engineering structures, real estate objects and more. For any economic system, investment activity is an important component of the economy. The investiture attractiveness of the enterprise should be considered because of the prospects, profitability, efficiency and minimization of the risks of investment investments in its development. It is determined that the investment strategy of the enterprise is a component of its overall economic development strategy which involves the effective application of various forms of investment in order to ensure the high market value of the enterprise, its investment attractiveness and sustainable pace of development. One of the main conditions for effective investment activity is to determine the correct investment strategy and tactical conditions for its implementation, taking into account the system of crisis management formed at the enterprise.
Theoretical principles of investment activity of enterprises
Keywords: ефективність; efficiency; інвестиції; investments; інвестиційна діяльність; investment activity; підприємство; enterprise; інвестиційна привабливість; investment attractiveness; системний підхід; systematic approach